2012
DOI: 10.1016/j.mehy.2012.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Argentum–quarz solution in the treatment of anorectal fistulas: Is it possible a conservative approach?

Abstract: Patients suffering from chronic intestinal diseases (Crohn's disease, Ulcerative Colitis, Indeterminate Colitis) are prone to the development of pyogenic complications. These complications are most commonly in the form of perianal or intraabdominal abscesses and/or fistulas. The treatment of these complications are managed differently but, after an initial treatment based on medical or minimally invasive management, the solution of the pathological condition is always achieved by a surgical procedure. In the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…This late phase is also described as the "sustained effects phase" in which silver proteinate experiences a progressive ionization, causing a slow but long-acting effect. It also known that SN has an antiseptic effect, 3 which is based on the protein denaturalization of the bacterial cell wall and membrane. Antimicrobial properties of silver are dependent upon release of biologically active silver ion (Ag + ) from SN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This late phase is also described as the "sustained effects phase" in which silver proteinate experiences a progressive ionization, causing a slow but long-acting effect. It also known that SN has an antiseptic effect, 3 which is based on the protein denaturalization of the bacterial cell wall and membrane. Antimicrobial properties of silver are dependent upon release of biologically active silver ion (Ag + ) from SN.…”
Section: Discussionmentioning
confidence: 99%
“…1 In 2014 Attaallah et al first reported encouraging results supporting conservative treatment of anal fistula using a silver nitrate (SN) 1% solution, with a complete resolution rate up to 52%. 2 SN is known to have an antiseptic action and the capacity to produce a chemical burn destroying the surrounding granulation tissue 3 favouring cicatrization.…”
Section: Introductionmentioning
confidence: 99%
“…Another noninvasive method in fistula is treatment using silver nitrate (SN) 1% solution. SN is known to have an antiseptic action and the capacity to produce chemical burn destroying the surrounding granulation tissue favoring cicatrisation (14) .…”
Section: Complexmentioning
confidence: 99%